Nonhuman language agents in online collaborative communities: Comparing Hebrew Wikipedia and Facebook translations. (March 2018) - Vaisman, Carmel L.; Gonen, Illan; Pinter, Yuval
Highlights: Unregulated media spaces of the same speech community developed very different language policies. Hebrew Wikipedia has a strict language policy seeking a neutral path between high register and slang. Hebrew Facebook lacked language standards focusing on practicality and speed of completion. Discursive practices are influenced by technical affordances that act as nonhuman language agents. Abstract: Online mass collaborations act as unregulated superdiverse language spaces, however, grassroots policing may impose uniformity and reproduce hegemony. This study compared language policies in Hebrew Wikipedia and the Hebrew Facebook translation app. Hebrew Wikipedia designed a strict linguistic guide that promotes a neutral Hebrew register, rejecting both colloquial and high registers, enforced by an algorithm post factum. The Hebrew Facebook translators' community maintained a decentralized approach, lacking the affordances for hierarchies of expertise, focusing on the practicality of the language and the speed of project completion. The comparative design within the same speech community stressed the role of affordances as nonhuman language agents in the social process of language policy.